Religion and race : African and European roots in conflict--a Jamaican testament - Lawson, Winston Arthur, 1944- (New York : P. Lang, 1996)
Religion and Race: African and European Roots in Conflict - A Jamaican Testament is an investigation of the significant role of three churches, both European and Afro-Jamaican, and how their theologies, cosmologies, and cultural norms influenced the development of Jamaican colonial society.
This study focuses on the dramatic interplay between the socio-cultural assumptions and values of the dominant planter groups and those of their Afro-creole workers, and the persistent problems that resulted from the perennial clash of such competing value systems, especially from 1823 to the early 1830s. Special attention is given to the role of key factors of culture, colour, and race, all operating within a distinctly religious framework that variously challenged or reinforced the status quo.
The parallels with the 1831 Nat Turner rebellion in the U.S.A. are noted and the implications for social harmony raised.
Ch. 1. The African roots of syncretism in Jamaican religion tradition: its contents, context and contributions. Traditional African cosmology ; Debating African cultural survival and its significance ; The ethics of Myalism: syncretized native religion and social control ; Creolization and early missionary developments ; Obeah: the non-religious Creole control mechanism and Christian cosmology ; European and Afro-Creoles in conflict: cosmologies, ethics and interests -- ch. 2. The historical and theological roots of the Anglican, Methodist and Baptist churches in nineteenth century Jamaica. The impact of absenteeism ; The churches' power struggle and cultural intolerance ; Impact of the churches' instruction ; Other early examples of the dilemma -- ch. 3. The churches' philosophy in operation: the persistent problems faced. Problems of judging Afro-Creole cultural expressions ; The churches' response to Afro-Jamaincan's assertiveness and planter pressure ; Examples of caution and vacillation -- ch. 4. The native Baptists at war: repercussions in education and nationalism. Conflicting perspectives on 1831 realities ; Understanding rebel leader Sam Sharpe ; Education and cultural nationalism.
Includes bibliographical references (pages 207-220).
NLJCols20082021
Keywords: Jamaica -- Religion -- 19th century; Jamaica -- History -- 19th century; Jamaica -- Race relations; 15.85 history of America; Race relations; Religion; Jamaica; Synkretismus; Kirche; Ethnische Beziehungen; Soziale Schichtung; Religion; Jamaika; Acculturatie; Culturele identiteit; Godsdienst; 15.85 history of America; Jama ique -- Religion -- 19e si ecle; Jama ique -- Relations interethniques; Geschichte 1800-1831.; Geschichte 1800-1900.; 1800-1899; History